2016
DOI: 10.21061/jvs.37
|View full text |Cite
|
Sign up to set email alerts
|

How are Institutions of Higher Education Implementing First-Year Transition Courses for Veterans?

Abstract: To better support veterans in their transition from the military to college, current literature recommends the use of a first-year transition course. However, it does not suggest how to implement this intervention nor if this tool is indeed effective at increasing retention and persistence toward graduation. In this pilot study, five institutions of various sizes and locations were surveyed to discover common themes related to their courses' structure, objectives, assignments, and assessment practices. The goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Ideally, transition support could be provided on an ongoing basis to student veterans throughout the first year of their studies. A number of institutions in the US have introduced firstyear transition courses for student veterans, which aim to provide: orientation to campus; introduction to campus resources; academic skills; connection to support staff; reflection on personal challenges and identity issues; connection to peers; and identification of goals (McMenamin & Kurzynski, 2016). Undertaking bridging or foundation courses before commencing degree study might also prove helpful for some student veterans.…”
Section: University Support For Veteransmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, transition support could be provided on an ongoing basis to student veterans throughout the first year of their studies. A number of institutions in the US have introduced firstyear transition courses for student veterans, which aim to provide: orientation to campus; introduction to campus resources; academic skills; connection to support staff; reflection on personal challenges and identity issues; connection to peers; and identification of goals (McMenamin & Kurzynski, 2016). Undertaking bridging or foundation courses before commencing degree study might also prove helpful for some student veterans.…”
Section: University Support For Veteransmentioning
confidence: 99%
“…This support includes targeted outreach strategies, academic support and student services, counselling services, academic credit for military training and experience, and financial assistance in the form of discounts and scholarships (Cook & Kim, 2012). Studies have also shown the value of considering student veterans in higher education curricula and pedagogy; for example, developing first-year transition programs for student veterans (McMenamin & Kurzynski, 2016), and incorporating semester-length peer groups in classrooms with student veterans and non-veteran students (Blackwell-Starnes, 2018). Student Veterans of America also provides programs, resources, and support to veterans in higher education.…”
Section: Introductionmentioning
confidence: 99%
“…And Whitley, Tshudi, and Gieber (2013) recommend a similar learning community for student veterans with any mental health problems. McMenamin and Kurzynski (2016) propose a veteran-only transition course that emphasizes services and skills needed for a successful transition to academic pursuits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, developing online or blended courses can help connect those SSM/V who have other responsibilities in addition to school. Developing SSM/V first-year interest groups that allow students to complete general studies, transition (McMenamin & Kurzynski, 2016), or core courses as a cohort can allow them to build community with those who have similar service or veteran experience. To that end, Blackwell-Starnes (2018) found that peer groups helped SSM/V develop a sense of belonging on campus and in the classroom.…”
Section: Implications For Student Affairs Professionals University Pementioning
confidence: 99%